Corporations May Hire More People With Disabilities Through Public Employment Support Services: Propensity Score Matching Analysis. (July 2019) - Kim, Won Ho; Nam, JeeEun Karin
This study investigated the effectiveness of employment support services provided to organizations in the context of the quota policies for hiring people with disabilities (PWD). Empirical analyses using the propensity score matching method were conducted on a representative sample of organizations in South Korea that had utilized the PWD employment support services offered by the Korea Employment Agency for the Disabled. In short, the employment support services provided to organizations appeared to be effective in enhancing employment of PWD. Specifically, the organizations that received the PWD employment support services (a) had a higher probability of hiring persons with disabilities, (b) fulfilled the mandated quota for PWD better, and (c) hired more individuals with severe disabilities compared with the organizations that did not receive such services. Implications and limitations of this study and directions for future research are discussed.